2017
DOI: 10.1016/j.amsu.2017.07.080
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic double-tract reconstruction after total gastrectomy for postoperative duodenal surveillance: Case series

Abstract: IntroductionWhen gastric cancer or carcinoid patients have coexisting diseases such as duodenal adenoma, FAP, or Crohn's disease, periodic observation of the duodenum is necessary.MethodsBetween August 2013 and April 2015, we performed four consecutive laparoscopic total gastrectomies with double tract reconstruction for duodenal surveillance. Three of the patients were diagnosed with gastric cancer, while the remaining patient was diagnosed with gastric carcinoid.ResultsNo deaths occurred, and three of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…[19][20][21] In the era of laparoscopic surgery, the problem of the best reconstruction technique after laparoscopic total gastrectomy has been widely discussed. Two meta-analyses 28,30 and one RCT. 29 demonstrated that IA is safer, with better cosmetic appearance, technically more feasible, leads to faster recovery of intestinal function, is less invasive compared to EA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] In the era of laparoscopic surgery, the problem of the best reconstruction technique after laparoscopic total gastrectomy has been widely discussed. Two meta-analyses 28,30 and one RCT. 29 demonstrated that IA is safer, with better cosmetic appearance, technically more feasible, leads to faster recovery of intestinal function, is less invasive compared to EA.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al 28 in a meta-analysis had shown that IA is characterized by better appearance, lower blood loss and faster recovery of intestinal function. In RCT 29 and meta-analysis 30 of 2015, LTG with IA was reported to be safer and more technically feasible that LTG with EA.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to favorable weight maintenance and nutritional outcomes for these patients [ 19 , 20 ]. Preservation of the duodenal passage in gastric reconstruction procedures may also be beneficial for access to the hepatobiliary system after surgery, in patients requiring Endoscopic Retrograde Cholangiopancreatography (ERCP) for various reasons post surgically [ 8 , 21 ].…”
Section: Effect On Postoperative Complicationsmentioning
confidence: 99%
“…
Introduction: Several interposition techniques have been described for reconstruction after total gastrectomy in FAP patients, in open (1) and laparoscopic assisted surgery (2,3,4). The Longmire technique has the advantage of allowing all the food to pass through the duodenum and better absorption of nutrients, such as iron (5).
…”
mentioning
confidence: 99%